The contribution of discrete sources to the sky temperature at 144 MHz - Hardcastle, MJ; Shimwell, TW; Tasse, C; Best, PN; Drabent, A; Jarvis, MJ; Prandoni, I; Roettgering, HJA; Sabater, J; Schwarz, DJ (EDP Sciences, 2021)
In recent years, the level of the extragalactic radio background has become a point of considerable interest, with some lines of argument pointing to an entirely new cosmological synchrotron background. The contribution of the known discrete source population to the sky temperature is key to this discussion. Because of the steep spectral index of the excess over the cosmic microwave background, it is best studied at low frequencies where the signal is strongest. The Low-Frequency Array (LOFAR) wide and deep sky surveys give us the best constraints yet on the contribution of discrete extragalactic sources at 144 MHz, and in particular allow us to include contributions from diffuse, low-surface-brightness emission that could not be fully accounted for in previous work. We show that, even with these new data, known sources can still only account for around a quarter of the estimated extragalactic sky temperature at LOFAR frequencies.